PENGARUH MODAL INTELEKTUAL DAN MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN - Triastuty, Siska; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to test the influence of intellectual capital and corporate governance mechanism tothe financial performance. The independent variables are intellectual capital, institutional capital, managerialownership, the proportion of the board of independent commissioner and the board of director. Meanwhile, thedependent variable in this research is the financial performance. The samples are 56 manufacturing companieswith 3 years observation in 2012-2014 periods. The samples have been selected by using purposive sampling.The financial statement data has been obtained from the Indonesia Stock Exchange (IDX). The analysis methodhas been carried out by using multiple linear regressions analysis and the SPSS 20 application.The results ofthis research show that, (1) intellectual capital has positive influence to the financial statement of the company.(2) Institutional ownership does not have any influence to the financial statement of the company. (3)Managerial ownership has positive influence to the financial statement of the company. (4) The proportion of theboard of independent commissioner has positive influence to the financial statement of the company. (5) Theboard of directors does not have any influence to the financial performance of the company.Keywords: Intellectual Capital, Coorporate Governance Mecanism, Financial Performance.